Effects of Vitamin D and E Supplementation on Prevention of Bronchopulmonary Dysplasia (BPD) in Premature Neonates: A Systematic Review and Meta-analysis - Farahbakhsh, Nazanin; Sharma, Deepak; Fatahi, Somaye; Fathi, Mobina; Vakili, Kimia; Deravi, Niloofar; Tutunchian, Zohreh; Ahsan, Elahe; Yaghoobpoor, Shirin; Tabatabaii, Seyed Ahmad (Current Pediatric Reviews, 2025)
BackgroundBronchopulmonary Dysplasia (BPD) has a multifactorial etiology. Vitamin E and vitamin D play an important role in lung development and can potentially be beneficial in the prevention of BPD.ObjectivesThe study aimed to compare the risk of BPD occurrence in preterm neonates supplemented with vitamin D or E versus those who did not get supplementation.MethodsThe literature search was conducted for this systematic review by searching the PubMed, Scopus, and Web of Science databases up to December 2022. Randomized controlled trials involved administering vitamin D or E to preterm neonates and examining the occurrence of BPD. We excluded non-English articles, and articles with non-relevant and insufficient data. We used the Critical Appraisal Skills Programme (CASP) checklist to assess the quality of the included studies. We used Egger’s test to evaluate the risk of bias among the included studies. Heterogeneity was also assessed through Q-test and I2. We applied the random effect model for analysis. A P-value less than 0.05 was considered as significant. All the statistical analysis in the current study was performed using STATA 14. The Relative Risk (RR) was calculated as the effect size with 95% Confidence Interval (CI).ResultsThree eligible studies seeking the role of vitamin D in the prevention of BPD were analysed. Meta-analysis revealed that receiving vitamin D supplementation can significantly reduce the risk of BPD in preterm infants (RR = 0.357, 95% CI: 0.189-0.675, I2 = 0.0%; p = 0.002). Similarly, for assessing the role of Vitamin E in the prevention of BPD, three eligible studies were analysed. Vitamin E supplementation was not found to play a significant role in the reduction of BPD (RR = 0.659, 95%CI = 0.243-1.786, I2 = 38.7%; p = 0.412).ConclusionVitamin D supplementation could be beneficial in preventing BPD in preterm infants. However, evidence is not enough regarding vitamin E's role in reducing the incidence of BPD in preterm infants.
Keywords: preterm